2016
DOI: 10.1007/s00280-016-3069-8
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I study of safety and pharmacokinetics of fruquintinib, a novel selective inhibitor of vascular endothelial growth factor receptor-1, -2, and -3 tyrosine kinases in Chinese patients with advanced solid tumors

Abstract: Fruquintinib showed an acceptable safety profile and preliminary evidence of anti-tumor activity in patients with advanced solid tumors. The recommended dose was determined to be either 4 mg QD on a continuous regimen or 5 mg QD on a 3-week-on/1-week-off regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 25 publications
2
26
0
Order By: Relevance
“…In phase I trials, fruquintinib demonstrated good pharmacokinetic properties, tolerable safety, and promising anti-tumor activity against multiple tumor types [13]. A further two-regimen comparison study was carried out [14], and a regimen of 5 mg once daily oral dose on a 3-week-on/1-week-off treatment cycle was determined as the recommended phase II dose (RP2D).…”
Section: Introductionmentioning
confidence: 99%
“…In phase I trials, fruquintinib demonstrated good pharmacokinetic properties, tolerable safety, and promising anti-tumor activity against multiple tumor types [13]. A further two-regimen comparison study was carried out [14], and a regimen of 5 mg once daily oral dose on a 3-week-on/1-week-off treatment cycle was determined as the recommended phase II dose (RP2D).…”
Section: Introductionmentioning
confidence: 99%
“…Fruquintinib, a highly potent and selective VEGFR 1/2/3 inhibitor, showed an acceptable safety profile and significant efficacy in a phase I study [ 14 ]. It is currently being evaluated in a randomized phase III study (FALUCA, NCT02691299, PI: Shun Lu, Shanghai Chest Hospital, China) that aims to compare fruquintinib with a placebo in NSCLC patients who either failed two lines of systemic chemotherapy or experienced intolerable toxicities.…”
Section: Introductionmentioning
confidence: 99%
“…Fruquitinib, a selective inhibitor of VEGF receptors 1, 2 and 3, is being investigated in the "FRESCO" phase 3 trial in a Chinese refractory mCRC population naive to anti-VEGF therapy. 37,38 This is based on phase 2 data where fruquintinib improved median OS to 9.3 m, v 6.6 m with placebo [HR 0.65; 95% CI 0.51-0.83; p<0.001]. 38 The "FRESCO-2" trial is being conducted in a similar population but allows previous treatment with anti-VEGF mAB, TAS-102 or regorafenib.…”
Section: Emerging Therapies Anti-vegf Strategiesmentioning
confidence: 99%